Efficient fiber shaped zinc bromide batteries and dye sensitized solar cells for flexible power sources. Issue 10 (28th January 2015) - Peng, Ming; Yan, Kai; Hu, Hsienwei; Shen, Dinghan; Song, Weixing; Zou, Dechun
Abstract : Flexible fiber shaped zinc bromide batteries and dye sensitized solar cells for a hybrid energy system with an overall efficiency of 3.4% are presented. Abstract : This work presents flexible fiber shaped zinc bromide batteries and dye sensitized solar cells for efficient energy conversion and storage. The rechargeable FBs based on zinc bromide chemistry achieved a capacity up to 19 mA h mL −1 and an energy efficiency of 69%. The 31.5 cm long flexible fiber dye sensitized solar cell (FDSC) based on a titanium dioxide bilayer exhibits an efficiency ( η ) of 4.01% (6.68% in the diffuse model), which is the longest single FDSC with the highest power output (5.99 mW). The hybrid energy system with these two types of flexible power fibers achieved a promising overall energy conversion efficiency of 3.4%. All the preparation is easy to handle and suitable for large scale production and this study may pave the way for flexible, lightweight, and efficient power sources.